Political theory an introduction - Heywood, Andrew; Chin, Clayton (Bloomsbury Academic, 2023)
An introduction to the contemporary study of political theory, covering all of the key concepts, theories, traditions and debates and controversies, from the early foundations of political theory to the present day --